2015
DOI: 10.1002/pros.23045
|View full text |Cite
|
Sign up to set email alerts
|

Reactive stroma in the prostate during late life: The role of microvasculature and antiangiogenic therapy influences

Abstract: Reactive stroma develops in the prostate of non-transgenic mice as a result of aging. The periacinar microvasculature is a candidate source for the recruitment of reactive stroma-associated cells, which may be derived either from perivascular-resident mesenchymal stem cells (MSCs) or from an endothelial-to-mesenchymal transition (EndMT) process. Thus, antiangiogenic therapy is a promising approach for preventing age-associated prostate malignancies by means of its negative interference in the development of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
1
16
0
1
Order By: Relevance
“…The occurrence of reactive stroma during prostate tumorigenesis has been previously characterized in genetically modified mouse models of prostatic lesions, including in studies by our group using TRAMP mice . Importantly, we found that the gradual increase in VIM expression from PIN to WDAC transition was paralleled by maintenance of αSMA levels in the stroma . In the present study, we further demonstrated that celecoxib and nintedanib administration, per se or in association, resulted in lower VIM reactivity and protein levels in TRAMP mice prostatic stroma.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The occurrence of reactive stroma during prostate tumorigenesis has been previously characterized in genetically modified mouse models of prostatic lesions, including in studies by our group using TRAMP mice . Importantly, we found that the gradual increase in VIM expression from PIN to WDAC transition was paralleled by maintenance of αSMA levels in the stroma . In the present study, we further demonstrated that celecoxib and nintedanib administration, per se or in association, resulted in lower VIM reactivity and protein levels in TRAMP mice prostatic stroma.…”
Section: Discussionsupporting
confidence: 81%
“…Tissue was cut into 5 μm thick sections and collected in silanized slides. Immunohistochemical reactions were carried out according to protocols previously described by our group . Antigens were detected using the following antibodies: mouse monoclonal anti‐PCNA (ab29) (Abcam, Cambridge, MA, USA), rabbit polyclonal anti‐CD31 (sc‐1506‐R) (Santa Cruz Biotechnology, Dallas, TX, USA), rabbit monoclonal anti‐CD3 (ab16669) (Abcam), rabbit polyclonal anti‐ERα (sc‐542) (Santa Cruz Biotechnology), rabbit polyclonal anti‐AR (sc‐816) (Santa Cruz Biotechnology), rabbit monoclonal anti‐vimentin (ab92547) (Abcam), and mouse monoclonal anti‐αSMA (ab7817) (Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…However, the present results showed that α‐actin increases according to the proliferative lesion progression in the prostate anterior lobe, confirming data already presented in literature. Montico et al () observed that α‐actin increased in the dorsolateral prostate in elderly and TRAMP mice, indicating stromal reaction linked to increase of age and neoplasia onset (Montico et al, ). In addition, Yu et al () showed that differences in α‐actin expression are linked to AR activity in smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PD‐L1 has been demonstrated to express on fibroblasts in the cancer microenvironment of non‐small cell lung cancer and on myofibroblasts in human colonic mucosal, which could limit T cell proliferative activities . The phenotype of CD34/VIM, CD34/α‐SMA and α‐SMA/VIM dual‐positive fibroblasts and myofibroblasts may be also involved in the progression of prostate malignancy . To define whether the PD‐L1 + cells possessed the property of fibroblasts or myofibroblasts in prostate cancer, we used three mesenchymal markers CD34, VIM, and α‐SMA to perform double‐staining assays with PD‐L1, respectively.…”
Section: Resultsmentioning
confidence: 99%